2016
DOI: 10.1186/s12918-016-0350-8
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics unravels functionalities of phosphorylation sites in Saccharomyces cerevisiae

Abstract: BackgroundCoordinated through a complex network of kinases and phosphatases, protein phosphorylation regulates essentially all cellular processes in eukaryotes. Recent advances in proteomics enable detection of thousands of phosphorylation sites (phosphosites) in single experiments. However, functionality of the vast majority of these sites remains unclear and we lack suitable approaches to evaluate functional relevance at a pace that matches their detection.ResultsHere, we assess functionality of 26 phosphosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Although some recent work elucidated the genetic underpinning of these metabolic changes ( Gaude and Frezza, 2016 , Hu et al, 2013 ), whether cancer metabolism is tuned via post-translational changes is still largely unknown. In yeast, several studies have shown that signalling has a broad importance in regulating the activity of metabolic enzymes involved in central carbon metabolism and other peripheral pathways ( Gonçalves et al, 2017 , Oliveira et al, 2015 , Raguz Nakic et al, 2016 ). By contrast, regulatory phosphorylation of metabolic enzymes in human cells remains largely uncharacterised.…”
Section: Introductionmentioning
confidence: 99%
“…Although some recent work elucidated the genetic underpinning of these metabolic changes ( Gaude and Frezza, 2016 , Hu et al, 2013 ), whether cancer metabolism is tuned via post-translational changes is still largely unknown. In yeast, several studies have shown that signalling has a broad importance in regulating the activity of metabolic enzymes involved in central carbon metabolism and other peripheral pathways ( Gonçalves et al, 2017 , Oliveira et al, 2015 , Raguz Nakic et al, 2016 ). By contrast, regulatory phosphorylation of metabolic enzymes in human cells remains largely uncharacterised.…”
Section: Introductionmentioning
confidence: 99%
“…However, functionality of the vast majority of phosphorylation sites remains unclear. Untargeted metabolomics was used to overcome some of these challenges to unveil the biological roles of functional phosphosites to regulate metabolic pathways and potentially cellular function …”
Section: Understand Biological Impact Of Metabolomicsmentioning
confidence: 99%
“…Already, mutation studies of important p-sites in combination with proteomics and flux analysis or untargeted metabolomics show the way forward [4446]. Considering the large number of p-sites estimated in this analysis, it is likely that such a daunting challenge will need to be addressed by a fusion of bioinformatics filtering analyses together with highly automated HTP omics and experimental processes that assess the phenotype of mutants [47,48].…”
Section: Discussionmentioning
confidence: 99%